Detection of herpesvirus-like DNA by nested PCR on archival skin biopsy specimens of various forms of Kaposi sarcoma. Issue 8 (August 1996) - Cathomas, G; McGandy, C E; Terracciano, L M; Itin, P H; De Rosa, G; Gudat, F
Abstract : AIMS: To detect herpesvirus-like DNA sequences, defining a new herpesvirus, human herpesvirus 8 (HHV8), in paraffin wax embedded skin biopsy specimens of the various forms of Kaposi sarcoma. METHODS: DNA was extracted from archival skin biopsy specimens of Kaposi sarcoma, other mesenchymal skin tumours and various inflammatory skin lesions of HIV seropositive and negative patients. HHV8 DNA was detected by using a nested PCR assay. Human beta-globin DNA served as an internal control. RESULTS: Twenty two samples of Kaposi sarcoma were analysed, comprising 12 of the endemic type, nine HIV associated and one transplantation related. HHV8 DNA was detected by nested PCR in all forms of Kaposi sarcoma. By contrast, no HHV8 DNA was detected in five mesenchymal skin tumours or nine biopsy specimens of unspecific inflammatory skin lesions of HIV seropositive and negative patients. CONCLUSIONS: Detection of HHV8 DNA in paraffin wax embedded tissue can be used to confirm a diagnosis of Kaposi sarcoma.